The psychic resilience on an example of some martial arts fighters - Pujszo, Małgorzata; Janowska, Patrycja; Stępniak, Robert (Journal of Education, Health and Sport, 2019)
There were 76 persons who practice different martial arts (Aikido, Muay Thai/ Kickboxing, Judo) and 25 persons who did not practice any form of recreational activity, who took part in the research about men psychic resilience. The data was gathered through completing the survey ‘The resilience Scale RS-13’ by Kareny Leppert. The test results were divided experimentally into three elements. There were significant changes in resilience along with the training experience observed. However; the changes in numbers and resilience’s elements trends did not provide unambiguous answer whether the experiment was successful or not.